AB0751 The epstein-barr virus infection in systemic sclerosis. (12th June 2018) - Efthymiou, G.; Liaskos, C.; Marou, E.; Dardiotis, E.; Tsimourtou, V.; Scheper, T.; Meyer, W.; Bogdanos, D.P.; Hadjigeorgiou, G.; Sakkas, L.I.
Abstract : Background: Epstein-Barr virus (EBV) infection has been considered trigger of various autoimmune diseases, including systemic sclerosis (SSc), mainly due to studies investigating cross-reactive responses amongst EBV and disease-specific antigens. Meticulous assessment of antibody reactivities to the most immunodominant EBV antigens in SSc has not been performed. Objectives: To assess ab reactivity against EBV viral capsid antigens (VCA), early antigens (EA) and EBNA-1 in SSc, and investigate their clinical relevance. Methods: Sera from 59 SSc patients, including 31 diffuse SSc (dcSSc) and 28 limited SSc (lcSSc), 43 matched multiple sclerosis (MS) as controls and 32 matched healthy controls (HC) were tested for IgG anti-EBV VCA, EA and EBNA-1 abs by immunoblotting, using EBV whole SDS extract as antigen substrate. Results: Percentages of EA and EBNA-1 reactivities were significantly higher in SSc patients compared to HC (EA: 33.9% vs 3.1%, p=0.001; EBNA-1: 89.8% vs 68.8%, p=0.012), but were comparable between SSc and MS. These differences remained when SSc was divided in dcSSc and lcSSc (EA: 32.3% in dcSSc and 35.7% in lcSSc, p dcSSc vs HC =0.002, p lcSSc vs HC =0.001; EBNA: 92.9% in lcSSc, p lcSSc vs HC =0.020). VCA positivity was comparable between SSc or its two subgroups and MS or HCs. Also, triple positivity for all three antigen categories was observed more frequently in SSc, dcSSc and lcSSc compared to HCs (32.2% in SSc, 29% in dcSSc and 35.7% in lcSSc vs 3.1% in HC, p=0.001, p=0.004 and p=0.001, respectively). Anti- EA was present more frequently in SSc patients with calcinosis compared to those without (75% vs 27.5%, p=0.014) and tended to be more frequent in patients with pulmonary fibrosis compared to those without (47.8% vs 25%, p=0.071). Conclusions: Antibodies against EBV appear to be more frequent in SSc than in healthy controls, and equally prevalent with MS, a disease known to be associated with anti-EBV antibody responses and a known risk factor for MS. Whether an EBV-specific response is also an initiating trigger of SSc remains to be investigated. Disclosure of Interest: G. Efthymiou: None declared, C. Liaskos: None declared, E. Marou: None declared, E. Dardiotis: None declared, V. Tsimourtou: None declared, T. Scheper Employee of: EUROIMMUN, W. Meyer Employee of: EUROIMMUN, D. Bogdanos: None declared, G. Hadjigeorgiou: None declared, L. Sakkas: None declared